Объяснение:
1) 2Fe(OH)3 + 3H2SO4 = Fe2(SO4)3 + 6H2O
2) CaCl2 + Na2CO3 = CaCO3↓ + 2NaCl
3) CuSO4 + 2NaOH = Cu(OH)2↓ + Na2SO4
4) BaCl2 + H2SO4 = BaSO4↓ + 2HCl
5) Mg(OH)2 + 2HNO3 = Mg(NO3)2 + 2H2O
6) ZnSO4 + 2KOH = Zn(OH)2↓ + K2SO4
7) 2HCl + K2SO3 = 2KCl + SO2↑ + H2O
Объяснение:
1) 2Fe(OH)3 + 3H2SO4 = Fe2(SO4)3 + 6H2O
2) CaCl2 + Na2CO3 = CaCO3↓ + 2NaCl
3) CuSO4 + 2NaOH = Cu(OH)2↓ + Na2SO4
4) BaCl2 + H2SO4 = BaSO4↓ + 2HCl
5) Mg(OH)2 + 2HNO3 = Mg(NO3)2 + 2H2O
6) ZnSO4 + 2KOH = Zn(OH)2↓ + K2SO4
7) 2HCl + K2SO3 = 2KCl + SO2↑ + H2O